Gender and power in Indonesian Islam leaders, feminists, Sufis and pesantren selves - Smith, Bianca J. (Asian Studies Association of Australia women in Asia series, 2014)
"This book discusses the understandings of gender and Islam in pesantren and Sufi orders in Indonesia. It contributes to the decolonization of the anthropology of Islam in Indonesia, confronting ideological and intellectual tropes of (neo)-colonialism in two ways. Firstly, it deconstructs categories denying the "authenticity" of Indonesian Islams on the basis of comparison with the Arab Middle East, and secondly, it critically examines the salience of expatriate and diasporic Middle Eastern Muslim feminist discourses and secular western feminist analyses in Indonesian contexts".